2021
DOI: 10.1016/j.apsb.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation regulates cullin-based ubiquitination in tumorigenesis

Abstract: Cullin-RING ligases (CRLs) recognize and interact with substrates for ubiquitination and degradation, and can be targeted for disease treatment when the abnormal expression of substrates involves pathologic processes. Phosphorylation, either of substrates or receptors of CRLs, can alter their interaction. Phosphorylation-dependent ubiquitination and proteasome degradation influence various cellular processes and can contribute to the occurrence of various diseases, most often tumorigenesis. These processes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 100 publications
0
30
0
Order By: Relevance
“…This metabolic reprogramming gives HCC cells a growth advantage by providing energy for cancer cell growth and other metabolic intermediates for various processes ( 14 ). As a multi-step process, its progress is tightly regulated by three key rate-limiting enzymes (Hexokinase, PFK and PKM2) ( 15 ). In this study, we established that the highly expressed DNAAF5 proteins in HCC promote the malignant progression of tumor cells by increasing PFKL protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This metabolic reprogramming gives HCC cells a growth advantage by providing energy for cancer cell growth and other metabolic intermediates for various processes ( 14 ). As a multi-step process, its progress is tightly regulated by three key rate-limiting enzymes (Hexokinase, PFK and PKM2) ( 15 ). In this study, we established that the highly expressed DNAAF5 proteins in HCC promote the malignant progression of tumor cells by increasing PFKL protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this implies that even under aerobic conditions, tumor cells preferentially perform glycolysis rather than the productive oxidative phosphorylation pathway. This effect is manifested by a high rate of glucose uptake, active glycolysis, and high lactate levels ( 15 ). Tumor cells also use this special metabolic method to obtain energy and materials for building cellular structures, enhancing malignant cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Snail1 is rapidly degraded in the cells and with a short half-life, due to the continuous ubiquitination and degradation by the proteasome (Brabletz et al, 2021). Several E3 ligases, including FBXL14, FBW7, β-TrCP, and FBXO11, have been shown to promote Snail1 ubiquitination and degradation (Chen et al, 2021;Díaz & de Herreros, 2016;Huang, 2010;Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Snail1 is rapidly degraded in the cells and with a short half‐life, due to the continuous ubiquitination and degradation by the proteasome (Brabletz et al, 2021). Several E3 ligases, including FBXL14, FBW7, β‐TrCP, and FBXO11, have been shown to promote Snail1 ubiquitination and degradation (Chen et al, 2021; Díaz & de Herreros, 2016; Huang, 2010; Zheng et al, 2014). On the other hand, protein deubiquitination, a process in which ubiquitin is removed from target proteins by deubiquitinases (DUBs), plays an important role in cancer progression including proliferation and metastasis in various tumors (Mennerich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleolar and coiled-body phosphoprotein 1 (NOLC1), a phosphoprotein, consists of a unique central repeat domain, and C-terminal and N-terminal domains [6][7][8]. Huang et al reported that NOLC1 was positively correlated with the tumorigenesis of non-small cell lung cancer (NSCLC) and might be utilized as biomarkers for the early diagnosis of NSCLC [9].…”
Section: Introductionmentioning
confidence: 99%